The Use of Discovery Method to Improve Students’ Learning Activities and Outcome in Learning Mathematics at Grade V in Public Elementary School 08 Nan Limo Mudik, Palupuh District, Agam Regency - Risna Nelly; Taufina Taufik; Irdamurni Irdamurni (Universitas Negeri Padang, 2019)
The research conducted based on the students’ learning activities and outcome in learning math about finding the area of the plane at grade V in Public Elementary School 08 Nan Limo Mudik, Palupuh District, Agam Regency was still low. After doing observation, it turned out that the teaching-learning process was less interesting and the use of media was less appropriate so that students’ ability to do problem solving, to convey the ideas, and to find by themselves the formula of the area of plane was low. Therefore, this research used discovery method conducted in the first semester, 2016/2017 academic year. This research consisted of two cycles. Every cycle consisted of four stages that are planning, implementing, observation, analysis, and reflection. The result of the research showed that by using discovery methods, there was the increase in students’ learning activities and outcome at grade V in Public Elementary School 08 Nan Limo Mudik. For the students’ learning activities, there was the increase from 70,38 in the first cycle to 83,75 in the second cycle. Based on that mark, the average mark of students’ learning activities was in very good qualification. The percentage of the students’ learning outcome also increased from 45 % by the average 71,10 in the first cycle to 95% by the average 84,65 in the second cycle. Thus, it can be concluded that the use of discovery method can increase students’ learning activities and outcome in learning math at at grade V in Public Elementary School 08 Nan Limo Mudik. In accordance with qualitative, the teaching-learning process using discovery method can increase students’ learning activities and outcome in learning math about finding the area of the plane. To summarize, the use of the discovery method succeeded to increase students’ learning activities and outcome exceeding the KKM. Therefore, the research can be closed.